Evaluating the Nexus between Farm Size, Fertilizer Input and Technical Efficiency of Rice Production in North West, Nigeria - ALABI, Olugbenga Omotayo; MAHARAZU, Ibrahim; ALUWONG, Jeremiah Samuel; BAKO, Jerry Oluwatosin; MUHAMMAD, Abdulrrahman Kabir (Agricultural Science, 2024)
Rice contributes a significant function in reducing food insecurity in sub-Saharan Africa including Nigeria. This study evaluates the nexus between farm size, fertilizer input, and technical efficiency (TE) of rice production, Nigeria. Data covered 200 rice farmers proportionally distributed in Kano and Kaduna states. The TE levels were obtained using parametric approach such as stochastic production efficiency frontier model (SPEFM) and descriptive statistics. The production constraints of rice farmers were evaluated using PCA (Principal Component Analysis). The average TE score of rice producers is 53.13% leaving an efficiency gap of 46.87% for improvement. Inferential analysis showed that the significant predictors influencing TE of rice production include fertilizer, farm size, agrochemicals, seed, and family labour. The addition of the first-order of the production predictors which is called the scale elasticity shows increasing RTS (return to scale) which is estimated at 1.958. The sources of TIE (technical inefficiency) of rice production were age, experience in rice farming, education level, members of cooperatives, and amount of credit accessed. The coefficient of variance ratio, the gamma is 0.7827, this connotes that 78.27% of variations in the output of rice were due to differences in TE. The major production constraints facing rice producers include lack of access to farm land (1st), high cost of fertilizers (2nd), and lack of agrochemicals (3rd). The cost of fertilizers should be reduced and made affordable for increased rice productivity and efficiency, secondly, easy access to farm land is necessary in terms of policy formulations and implementations.